GROWTH, ELECTRICAL AND MECHANICAL STUDIES OF L-ALANINIUM MALEATE - Dr. SEETHALAKSHMI K.,; Dr. SURAPANENI KRISHNA MOHAN, (International Journal of Pharma and Bio Sciences, 2016)
L-Alaninium maleate single crystal was grown by slow evaporation technique. Dielectric constant, dielectric loss and AC conductivity were determined to an accuracy of ± 2% with four different frequencies (1 kHz, 10 kHz, 100 kHz and 1 MHz) at various temperature ranging from 30 – 150 °C along (1 1 1) plane surface.The measurements of DC electrical conductivity was done using the conventional twoprobe technique for temperatures ranging from 40 – 150 °C. The microhardness studies for LAMA crystal have been carried out to find its hardnesss.